(untitled) (African Journal of Biomedical Research, 2020)
Periodontal diseases are common oral diseases. Records show high recovery rates of Streptococcus species is associated with untreated periodontitis. Data on variants of streptococcal species associated with periodontitis in Nigeria is limited. This study identified the species, subspecies and genetic relatedness of Streptococcus that occur among patients with chronic periodontitis using 16S rRNA Gene Sequence technique and phylogenetic analysis. Patients were recruited at Periodontal Clinic of Lagos University Teaching Hospital, Lagos Nigeria. Paper point specimens of subgingival plaque were collected from periodontal pockets and cultured by anaerobiosis on Fastidious Anaerobe Agar. Presumptive identification of the streptococcal species isolated was done by cultural and biochemical analysis. Molecular Identification was done by Sanger sequencing to confirm the identity of the isolates. Twenty-four (24) subgingival plaque samples cultured from 6 patients with chronic periodontitis yielded 24 anaerobic gram-positive isolates of which 20 were amplified by I6SrRNA primer. From this, 17/20 (85%) were identified as Streptococcus and 3/20 (15%) Staphylococcus species. The 16S rRNA showed the identity of these isolates at species and subspecies level. The species belonged to the anginosus (58.8%) and mitis (41.2%) groups. Phylogenetic analysis showed divergent periodontal strains. Our results revealed the species and subspecies of members of Streptococcus groups associated with chronic periodontitis in a Nigerian population. The severity of periodontitis in relation to the ecological niche created in periodontal pockets may have an impact on the proliferation of certain Streptococcal species.